An epigenetic modifier induces production of (10′S)-verruculide B, an inhibitor of protein tyrosine phosphatases by Phoma sp. nov. LG0217, a fungal endophyte of Parkinsonia microphylla - Gubiani, Juliana R. [UNESP]; Wijeratne, E.M. Kithsiri; Shi, Taoda; Araujo, Angela R. [UNESP]; Arnold, A. Elizabeth; Chapman, Eli; Gunatilaka, A.A. Leslie (Elsevier, 2017)
Incorporation of the histone deacetylase (HDAC) inhibitor, suberoylanilide hydroxamic acid (SAHA), to a culture broth of the endophytic fungus Phoma sp. nov. LG0217 isolated from Parkinsonia microphylla changed its metabolite profile and resulted in the production of (10′S)-verruculide B (1), vermistatin (2) and dihydrovermistatin (3). When cultured in the absence of the epigenetic modifier, it produced a new metabolite, (S,Z)-5-(3′,4′-dihydroxybutyldiene)-3-propylfuran-2(5H)-one (4) together with nafuredin (5). The structure of 4 was elucidated by spectroscopic analyses and its absolute configuration was determined by application of the modified Mosher's ester method. The absolute structure of (10′S)-verruculide B was determined as 5-[(10′S,2′E,6′E)-10′,11′-dihydroxy-3′,7′,11′-trimethyldodeca-2′,6′-dien-1′-yl]-(3R)-6,8-dihydroxy-3-methylisochroman-1-one (1) with the help of CD and NOE data. Compound 1 inhibited the activity of protein tyrosine phosphatases (PTPs) 1B (PTP1B), Src homology 2-containing PTP 1 (SHP1) and T-cell PTP (TCPTP) with IC50values of 13.7ï¿½ï¿½ï¿½3.4, 8.8ï¿½ï¿½ï¿½0.6, and 16.6ï¿½ï¿½ï¿½3.8ï¿½μM, respectively. Significance of these activities and observed modest selectivity of 1 for SHP1 over PTP1B and TCPTP is discussed.
Keywords: (10′S)-verruculide B; Epigenetic; Histone deacetylase inhibitor; Phoma sp. nov. LG0217; Protein tyrosine phosphatases